PENGEMBANGAN MEDIA POP-UP BOOK BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN SENI RUPA KELAS V SD NEGERI WINDUAJI 7 - Khofiatun; Liyana Safira; Izzatun Nawawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a local wisdom-based Pop-Up Book learning media for fifth-grade students in visual arts education at SD Negeri Winduaji 7. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of the study were 32 fifth-grade students consisting of 18 boys and 14 girls. Data were collected through observation, interviews, questionnaires, validation sheets, and learning outcome tests. The developed product was validated by media experts and material experts before being implemented in classroom learning. The results showed that the media achieved a validity score of 92.5% from media experts and 90.2% from material experts, categorized as very valid. Student responses reached 94.1%, indicating that the media was very practical. Furthermore, learning outcomes and creativity scores improved significantly after the implementation of the Pop-Up Book media. Therefore, the developed media is considered valid, practical, and effective for use in visual arts learning in elementary schools.